Do Post-IPO Invesments and Capital Structure Affect Financial Performance? Evidence From Indonesian Industrial Firms - Maya Liyanti; Mohamad Agus Salim Monoarfa; Dewi Indrayani Hamin (Jurnal Riset Akuntansi, Perpajakan dan Auditing, 2026)
This research seeks to investigate the influence of capital structure, indicated by the Debt-to-Equity Ratio (DER), and post-IPO investment, represented by asset growth, on the financial performance of companies, gauged by Return on Assets (ROA). The research concentrates on industrial sector firms that were registered on the Indonesia Stock Exchange from 2020 to 2024. An associative-causal design is employed in a quantitative manner. Purposive sampling was employed to select the sample, resulting in 150 data observations. The data was analyzed using SPSS software and multiple linear regression. Test for classical assumptions, include those for normality, multicollinearity, heteroscedasticity, and autocorrelation, were carried out before hypothesis testing. The findings show that post-IPO investment significantly and favorably affects the financial achievement of a company. On the other hand, there was no discernible effect of capital structure on financial performance. Nonetheless, it was discovered that these two independent factors had a simultaneous and substantial impact on financial success. Based on the coefficient of determination, the independent variables explained only 11.7% of the variation in financial performance; variables absent from the study model accounted for the remainder 88.3%.